KETIDAKEFEKTIFAN KALIMAT DALAM TEKS BIOGRAFI SISWA KELAS VIII SMP NEGERI 5 BUKITTINGGI - Emidar, Izzatur Rahmi, Harris Effendi Thahar, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The article was written for show the effectiveness of sentences in biography text on students at eight grade SMPN 5 Bukittinggi. The research is qualitative by using descriptive method. Based on the analysis of the data and the discussion, there are three conclusions. First, the uneffectiveness of the sentences based on structure has not subject and the sentences has not adverb. Second, the uneffetiveness of sentences based on word selection has three aspect, there are (1) the word is unmatch (2) The word is not standard and (3) the word is wastful. Third, the uneffectiveness of sentences based on punctuation, there are three aspect (1) the using of capital unmatch (2) The written of word unmatch (3) The using of conjuction unmatch.Â Kata kunci: ketidakefektifan , kata, teks biografi